2021
DOI: 10.1096/fj.202002414r
|View full text |Cite
|
Sign up to set email alerts
|

The systemic antiangiogenic effect of intravitreal aflibercept injection in a mouse model of retinopathy of prematurity

Abstract: Retinopathy of prematurity (ROP) is a leading cause of childhood blindness and intravitreal anti‐vascular endothelial growth factor (VEGF) injection is becoming a first‐line choice for treatment of ROP. However, there is a major concern that intravitreally injected anti‐VEGF agents could escape from the eye into the systemic circulation and impair systemic development. Moreover, escaped anti‐VEGF agents could have an effect on the retina of the fellow eye. In this study, we investigated the hematogenous effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
(49 reference statements)
2
15
0
Order By: Relevance
“…We found that IVB displayed a short-term inhibitive effect on BW gain in infants with ROP, which is consistent with our previous research using a mouse model of ROP [12]. All of the previous clinical reports focusing on BW gain after intravitreal anti-VEGF injection analyzed only the long-term effect [13][14][15].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that IVB displayed a short-term inhibitive effect on BW gain in infants with ROP, which is consistent with our previous research using a mouse model of ROP [12]. All of the previous clinical reports focusing on BW gain after intravitreal anti-VEGF injection analyzed only the long-term effect [13][14][15].…”
Section: Discussionsupporting
confidence: 91%
“…A higher dose per BW of bevacizumab is administered to a smaller infant because the bevacizumab dose for ROP treatment is commonly fixed at 0.625 mg/0.025 ml [6]. Animal studies using mice also showed that increasing the anti-VEGF drug dose per BW suppressed BW gain to a greater extent [12,18]. Therefore, we should consider the use of lower doses of anti-VEGF agents, particularly in infants with smaller BW, because previous reports suggested that lower-than-standard doses were also effective for ROP [19,20].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…This property might be particularly useful, for example, for the treatment of retinopathy of prematurity, since it has been reported that treatment with anti-VEGF agents with significant systemic exposure might have detrimental neurodevelopmental effects ( 64 , 65 ). Consistent with our results of systemic exposure following intravitreal injection of Eylea, fellow eye effects in OIR have been reported ( 62 ). While the present, short-term experiments do not discriminate between one and two heparin-binding domains, based on earlier work on VEGF isoforms, one might expect that, initially, the more diffusible V23 might be equally effective, but on a longer-term basis, the stronger interaction with the matrix of V233 or V1233 might prove advantageous ( 8 ).…”
Section: Discussionsupporting
confidence: 93%
“…Control IgG, Eylea, and Avastin, had minimal binding. However, it should be noted that there are reported changes in HPSG composition in human vitreous humor with aging that might affect interaction with these proteins ( 62 , 63 ).…”
Section: Discussionmentioning
confidence: 99%